The Relationship between Knowledge and Attitudes towards Physical Changes in Premenopausal Women at the Samkai Health Center, Merauke - Nuraini,; Devy Putri Nursanti,; Erma Retnaningtyas,; Putri Eka Sejati, (Journal of Health Science Community, 2024)
Premenopausal is often not a concern for most women because they consider it a natural event, a small number consider it something bad or taboo to talk about openly. This study aims to determine the relationship between knowledge and attitudes towards physical changes in Premenopausal women at the Samkai Community Health Center, Merauke. This research uses a research design Analytical Observational with approach cross sectional. With technique accidental sampling The sample obtained was 48 respondents, the independent variable (knowledge and attitude) and the dependent variable (Physical changes in premenopausal women) using a questionnaire. Statistical tests are used Chi-Square to find out the relationship between the two variables. The results of research from 48 respondents showed that most respondents had poor knowledge about the physical changes of premenopausal women, namely 26 respondents (54.2%), most respondents had a negative attitude about the physical changes of premenopausal women, namely 25 respondents (52.1%), and It was found that most of the physical changes during premenopausal were partially felt, namely 27 respondents (56.3%). Analysis uses statistical tests Chi-Square a relationship was found Knowledge of physical changes in premenopausal women namely p value = 0.011 < 0.05, and there is a relationship attitudes towards physical changes in premenopausal women namely p value = 0.004 < 0.05. Necessity the role of health workers in providing education about the physical changes of premenopausal women so that women entering premenopausal can have a positive attitude by exercising regularly and taking care of themselves.